Implementasi Assessment Berbasis Articulate Storyline 3 Pada Model Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar dan Sikap Ilmiah Siswa SMA Negeri 3 Jember - Wulandari, Pria Nur; Maryani, Maryani; Supriadi, Bambang; Permatasari, Ika; Budiana, Santi (Navigation Physics : Journal of Physics Education, 2024)
This research is classroom action research which aims to obtain an overview of PTK learning using a guided inquiry model, especially on hydrostatic pressure material which can improve students' physics learning outcomes. This PTK was carried out at SMA Negeri 3 Jember in class XI MIPA 2 in the 2023/2024 academic year. This research was carried out in two cycles, in each cycle there were planning, implementation, observation and reflection stages. The data analysis used in this research is descriptive qualitative, quantitative and N-gain tests. The problem of this research is in the form of student learning outcomes whose scores are still much below the KKM (77) from 33 students who did not complete as many as 90.90% or 30 students and students who completed as many as 9.09% or 3 students. The research results showed that the average value in cycle I was 37.57 and in cycle II was 84.24. So the increase in the average data on student learning outcomes in cycle II was greater than cycle I, namely 84.24 > 37.57. This is also proven by the analysis of scientific attitudes, the average result in cycle I was 50.28% and in cycle II it was 80.96%. So the increase in the average data on students' scientific attitudes in cycle II was greater than cycle I, namely 80.96% > 50.28%.